AGREEMENT BETWEEN THE PESHITTA AND OLD GREEK AND THE TEXTUAL CRITICISM OF EZEKIEL IN THE HEBREW BIBLE - H F Van Rooy (Acta Theologica)
Of the fifteen examples discussed in this contribution, a different Vorlage is likely to underlie the Old Greek and the Peshitta in Ezekiel 10:1, 10:2 (second example), 11:7, 12:4-7 and 12, 16:23, 17:22, 21:17 and 23:43. For this last example, a new proposal is made for a reconstruction of the common Vorlage for the two versions. A different Vorlage is possible, but less certain, for Ezekiel 7:2, 11:2 and 12:25. The differences between the Masoretic Text, on the one hand, and the two versions, on the other, can be ascribed to a similar translation technique, or other factors in the case of Ezekiel 10:2 (first example), 11:15, 13:5 and 17:7, although a different Vorlage may be considered. In light of these examples, agreement between the Peshitta and the Old Greek against the Masoretic Text must be evaluated for every instance, bearing in mind the possibility of a different Vorlage.